Plasticity in Daphnia eye size is determined by intra-generational environmental conditions - Sha, Yongcui; Hansson, Lars Anders ; 0000-0002-3035-1317 (Proceedings of the Royal Society B: Biological Sciences, 2025)
Variation in the structure and size of the eye in relation to light environments is well-documented across animal taxa. However, the long-term effects of ultraviolet radiation (UVR) on eye size across generations remain understudied, despite natural fluctuations in UVR being common in aquatic habitats. Here, we used Daphnia magna to test whether an evolutionary history of UVR threat modifies plasticity and transgenerational responses in eye size. We conducted a reciprocal split-brood experiment across three parthenogenetic generations using two groups maintained under either UVR or non-UVR conditions for over 150 generations, enabling the potential accumulation of adaptive responses and the establishment of distinct evolutionary lineages for comparison. We found strong plasticity in eye size, primarily shaped by current environmental conditions rather than transgenerational effects. Smaller eyes developed in response to UVR but rapidly reverted to larger dimensions in its absence. Furthermore, changes in relative eye size were associated with fitness-related traits, including swimming behaviour and reproductive output, although these relationships varied in strength and direction between UVR-exposed and unexposed individuals. Our study highlights the role of environmental stressors and evolutionary history in shaping sensory adaptations, providing conceptual advances on how sensory traits among aquatic invertebrates may rapidly evolve under changing environmental conditions.
Publisher Copyright: © 2025 The Author(s).
Keywords: evolutionary history; light; phenotypic plasticity; trade-offs; transgenerational effects; ultraviolet radiation